Mengintegrasikan Praktik SDM Strategis untuk Mendorong Perubahan dan Inovasi Organisasi di Papua Barat: Tinjauan Pustaka - Yesnat, Yeskiel; Ady, Sri Utami (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the impact of strategic Human Resource Management (HRM) practices on organizational change and innovation in Papua Barat. The research employs a qualitative literature review method by analyzing relevant journals and academic articles from indexed sources to understand the relationship between HR practices, an organization's ability to change, and innovation. The findings indicate that strategic HR practices, such as employee skill development, empowerment, and structured performance management, have a positive impact on an organization's adaptability and capacity for innovation. Further discussion reveals that the implementation of HR practices supporting organizational change requires attention to local contextual factors in Papua Barat, such as limited infrastructure and low levels of workforce formality. In conclusion, the integration of strategic HR practices can enhance an organization's capacity to respond to changes and foster innovation. The implications of this study provide insights for organizations in Papua Barat to adopt adaptive HR strategies. Future research suggestions include exploring the application of strategic HR practices in specific industries in Papua Barat and conductng quantitative studies to measure the practical impact of these implementations.